ANALISIS PETROFISIKA DENGAN METODE DETERMINISTIK DAN PROBABILISTIK SERTA PERHITUNGAN VOLUME HIDROKARBON DENGAN METODE WELL BASIS PADA SUMUR MG-04 DI STRUKTUR MUSI, CEKUNGAN SUMATERA SELATAN PT. PERTAMINA EP REGION SUMATERA - Sari, Mega; Nugroho, Hadi; Hidajat, Wahju Krisna; Satriawan, Oki (Geological Engineering E-Journal, 2013)
Well logging is a measurement technique to obtain the subsurface data using instrument inserted intowellbore, to evaluate formation and rock characteristics identification beneath the surface. Formation evaluationaims to identify zones of reservoir rock, formation fluid type, and to obtain petrophysical parameters of reservoirrocks such as shale volume, rock porosity, permeability, water saturation at the research area, the well MG-04 weredrilled in the Musi Structure, South Sumatra Basin, PT. Pertamina EP. The purpose of this research is identifying productive layer on an exploration well in Musi Structure, SouthSumatra Basin. In addition, to determine the value of petrophysical rock parameters which recorded in a log curvesgenerated during logging and calculating the volume of hydrocarbon in exploration well as a consideration, priorto further exploration and exploitation. This research using descriptive methods and petrophysical analysis. The descriptive method includesliterature study of the basics concept on determining rock petrophysical parameters to be used. The analyticalmethod using deterministic and probabilistic method to determine petrophysical parameters, also âwell basisâmethod to calculate the volume of hydrocarbons. Based on wireline logs analysis, well MG-04 known has two reservoir zones, namely oil reservoir in zone 2and gas reservoirs in zone 4. In zone 2, the reservoir rock is shaly sandstone with little amount of glauconite. Inzone 4, the reservoir rock is limestone, so this is a necessary to analyze the shaly sandstone with different methodsto the interpretation of limestone to obtain the correct value of petrophysical parameters. After calculation ofpetrophysical parameters in deterministic and probabilistical way with âwet-clayâ models, obtained two log plotmodels that have close values, and it is known that the oil reservoir in zone 2 not potential for production, but gasreservoir in zones 4 the potential to do exploitation/ production. After the interpretation of petrophysicalparameters, it is known in zone 4 has a net pay thickness 68.43 m, total porosity percentage 28.42 to 29.72%,effective porosity 25.57 to 26.32%, permeability 56376,2 mD, water saturation 13.49 to 15.35% and shale volume 5to 10.5%. After obtaining reservoir petrophysical parameters, next step is hydrocarbon volume calculation using theâwell basisâ method, supported by pressure build up (PBU). Based on this analysis, it is known that total volume ofgas in the reservoir hydrocarbon type is estimated at 5088.4 MMSCF.